Representações verbo-visuais da cidade de Aracaju em folhetos de cordel - Rocha, Jeane Carozo (2021)
This work intends to talk about the representations of Aracaju city in the Twine Literature through a verb-visual analyze of chapbooks, considering some aspects like: ambience, memories, symbols, popular characters and personalities. For that propose, the chapbooks História de Aracaju (2006), Aracaju ontem e hoje! (2014) e Aracaju como eu vejo (2014) were chosen. Trying to reach the objective, we took as theorical reference, in the investigation and also in the analyses, as far as the aspects culture, erudite culture, of popular big crowd Lopes (1983), Laraia (1986), Burke (1989), Lara (2004), Arantes (2006), Correa, Correa e Anjos (2011); about the Cordell Literature, in its turn, , Diégues Jr. (1975), Tavares (1998), Assaré (2000), Andrade (2005), Fortaleza, Viana e Viana (2005), Silva (2012), Morais (2013), Bento e Diniz (2014), Filho (2015), Melo (2016), Freitas, Nascimento e Freire (2017), Nascimento (2018) e Mendonça (2018); as for ambience element Dimas (1985); as for Aracaju city Cabral (1948), Alves (2003) e Alves e Schomacker (2013); as for verb-visual language aspects in Twine Literature Roiphe (2011, 2013); as for memory Moisés (1974) and, lastly, as for aspects of, the personalities and symbols, Silva (2014). Dealing with the methodological experiments the work is qualitative that is recovered by many sources, such as: scientific articles, dissertations, twine chapbooks, books and thesis, as well as visits to libraries, museums, chapbook points of sale, cultural walking to many places in Aracaju, besides the participation in many courses, minicourses and workshops, all of these in order to collecting information about the search object. Lastly, as this work results, product of cultural, historic, religious, touristic a symbolic analysis of the chapbooks, it was found the existence of a representation of the Aracaju city in the first chapbook in a linear way, that is, since its emergence, through a period of development, achieving nowadays; second, by the simultaneous reading of the verbal and visual languages, the use of language figures as anaphors, slang, metaphors and prosopopoeial or personification of the above-mentioned elements, it was possible acquire as result the assembly of a representation about Aracaju starting of twine chapbooks considering authentic documents and not through school books as usually; to finish, this is another study that had the preoccupation of contribute to the permanence of the Twine Literature in the academy, ratifying its value by the demonstration of its main aspects, especially regarding the simultaneity of the verb-visual readings that compose the chapbooks not yet signed and disseminated in the Twine Literature studies demonstrated in the analyzes of the Aracaju city representations, as was made in this research, product the popular poets creativity.